Behovet for en jordskifteutdanning i Nord-Norge - Ravna, Øyvind (2009)
The Norwegian education system has gone through fundamental changes in the last decades. The educational monopoly the University of Life Sciences has had in educating land consolidation judges is proposed removed, and it’s time for innovative thinking. In northern- and parts of mid-Norway, new programmes to educate land consolidation judges can be reasoned not only because of the problems in recruitment of judges, but also in the requirement in the Constitution that judges need qualifications to safeguard Sámi language and culture. There it is a particular need to emphasize the situation in Sámi reindeer husbandry. This paper examines the need for an alternative land consolidation education to improve recruitment of judges and safeguard consideration of Sámi language and culture